The Association between Breakfast Macronutrient Composition and Body Weight, in Preadolescence: An Epidemiological Study among Schoolchildren - Stamatia Kokkou; Venetia Notara; Aikaterini Kanellopoulou; George Antonogeorgos; Andrea Paola Rojas-Gil; Ekaterina N. Kornilaki; Areti Lagiou; Demosthenes Panagiotakos (MDPI AG, 2022)
Over the last few decades, childhood overweight and obesity tend to reach epidemic proportions. The present study aimed to examine whether the composition of breakfast, through the prism of its macronutrient content, could play a part in the development of excess body weight in children. A sample of 1728 Greek students from 47 primary schools was enrolled for the purposes of this study. Their weight and height were measured and their Body Mass Index was calculated and classified according to the International Obesity Task Force criteria. Their dietary habits, breakfast foods of choice, and physical activity were assessed through the use of a self-completed questionnaire. Further assessment of breakfast composition was carried out in order to evaluate its macronutrient content. Initial analysis, which was only energy-adjusted, showed a negative association between body weight and breakfast protein content and a positive association for lipid content. After further adjustment for age, sex, level of adherence to the Mediterranean diet, and physical activity, there was a significant negative association between breakfast protein and excess body weight in children (p = 0.029), as well as a significant positive association of breakfast lipid content (p = 0.028). Breakfast macronutrient content seems to have an effect on body composition in children, independently of overall adherence to the Mediterranean diet and physical activity, however further research is needed in order to elucidate potential pathways.